Identifying cancer highly-expressed membrane receptors for targeted drug delivery. (1st January 2012) - Huang, Wei-Chih; Lin, Feng-Mao; Chang, Tzu-Hao; Liao, Kuang-Wen; Huang, Hsien-Da
Currently, the accompanying side effects of anti-cancer drugs owing to incorrect delivery to normal tissues should be reduced. We present a database (MRTDD) with identified cancer highly-expressed membrane receptors (CHMRs) which can be used in targeted drug delivery. To evaluate the probability of occurrence of incorrect delivery, we calculate tissue index for each CHMR and expect to identify good candidates. The information provided includes: (1) genomic annotations; (2) gene expression profiles of membrane receptors in cancer tissue vs. corresponding normal tissue, normal tissues of body and cancer cell-lines; (3) available antibody services of manufacturers. MRTDD is available athttp://mrtdd.mbc.nctu.edu.tw/ .